Changes & challenges in smart grid towards smarter grid - Jain A.; Mishra R. (My University, 2025)
Conventional resources are replenished day by day and are very limited but the need of electricity is increasing day by day. So in the todays scenario, energy alternatives is in trend to use that not only fulfils the need of the residential consumers but also commercial consumers. To overcome the different problems like interrupted and unreliable supply, high cost of the electricity etc., smart grid comes into the existence. Smart grid is considered as the 'grid of tomorrow' or 'vision of the future'. This paper gives an idea of the smart grid, its advantages, changes and challenges in power Sector. It also gives us an idea about the merits of Smart Grid over Conventional power system network. © 2016 IEEE.